2002
DOI: 10.1074/jbc.m106699200
|View full text |Cite
|
Sign up to set email alerts
|

Apicidin, a Histone Deacetylase Inhibitor, Induces Apoptosis and Fas/Fas Ligand Expression in Human Acute Promyelocytic Leukemia Cells

Abstract: We previously reported that apicidin arrested human cancer cell growth through selective induction of p21 WAF1/Cip1 . In this study, the apoptotic potential of apicidin and its mechanism in HL60 cells was investigated. Treatment of HL60 cells with apicidin caused a decrease in viable cell number in a dose-dependent manner and an increase in DNA fragmentation, nuclear morphological change, and apoptotic body formation, concomitant with progressive accumulation of hyperacetylated histone H4. In addition, apicidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
127
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(135 citation statements)
references
References 45 publications
(47 reference statements)
6
127
0
2
Order By: Relevance
“…A cowpox virus protein that inhibits caspase-8 and -10 was used to show that apoptosis in response to oxamflatin was mediated by the intrinsic pathway in a T-cell leukemia cell line. In contrast, other HDAC inhibitors such as apicidin have been shown to activate the death receptor pathway in leukemia cell lines [28]. Others have shown that administration of tumor necrosis factor-related apoptosisinducing ligand (TRAIL), known to activate the death receptor pathway, potentiates the apoptotic response in combination with HDAC inhibitors [29].…”
Section: Discussionmentioning
confidence: 99%
“…A cowpox virus protein that inhibits caspase-8 and -10 was used to show that apoptosis in response to oxamflatin was mediated by the intrinsic pathway in a T-cell leukemia cell line. In contrast, other HDAC inhibitors such as apicidin have been shown to activate the death receptor pathway in leukemia cell lines [28]. Others have shown that administration of tumor necrosis factor-related apoptosisinducing ligand (TRAIL), known to activate the death receptor pathway, potentiates the apoptotic response in combination with HDAC inhibitors [29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown HDAC inhibitor-induced upregulation of Fas, [18][19][20] FasL, 23 and Bax 31 and downregulation of Bcl-X L . 29,32 On the contrary, we did not observe changes in Fas and Bcl-X L expression following treatment of OST, U-2 OS, and HeLa cells with FR901228 (Figure 3b).…”
Section: Discussionmentioning
confidence: 99%
“…6 In HDAC inhibitor-induced activation of death receptor-mediated apoptosis, upregulation of Fas and FasL occurs in cells derived from neuroblastoma, 18 promyelocytic leukemia, 19 and uveal melanoma. 20 In addition, downregulation of FLIP-L protein was reportedly induced by treatment of chronic lymphocytic leukemia cells with the HDAC inhibitors FR901228 and MS-275.…”
Section: Introductionmentioning
confidence: 99%
“…6 Moreover, HDAC inhibitors were found to induce apoptosis characterized by typical morphological changes. 7,8 Conversely, HDAC inhibitors were reported to be neuroprotective via enhancing the acetylation of SP1, a cytoprotective transcription factor, and that this process is necessary for the induction of antioxidant proteins. 9 Further, an HDAC inhibitor, phenylbutyrate, was found to prolong markedly life span in Drosophila, presumably through modulation of gene expression.…”
Section: Introductionmentioning
confidence: 99%